10-3x=-x+9

Simple and best practice solution for 10-3x=-x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3x=-x+9 equation:


Simplifying
10 + -3x = -1x + 9

Reorder the terms:
10 + -3x = 9 + -1x

Solving
10 + -3x = 9 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
10 + -3x + x = 9 + -1x + x

Combine like terms: -3x + x = -2x
10 + -2x = 9 + -1x + x

Combine like terms: -1x + x = 0
10 + -2x = 9 + 0
10 + -2x = 9

Add '-10' to each side of the equation.
10 + -10 + -2x = 9 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = 9 + -10
-2x = 9 + -10

Combine like terms: 9 + -10 = -1
-2x = -1

Divide each side by '-2'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| (7x+3)+(7x-3)= | | 3k+2=26+7k | | 60+6y-15=17y-11-3y | | 5p(p+2)+4(p+4)= | | -14(-8)= | | 4x+9=2x-21 | | x^5-3x+4x^2+x-2=0 | | 4(2x+5)(-8)=36 | | -27=44-d | | 5(b+6)+8=73 | | 5c^2+34c+45=0 | | -3(s-18)=12 | | 13.2=1.2w | | 5x+-6=4x | | r^2=-21-10r | | 8(-15)+(-9(-15))=15 | | -8=-(a+4) | | -1=g-16 | | r^2=-21r-10r | | 9(x+3)-12x=3(x-6)-12 | | -2(s+4)=6 | | -3(n-2)=-n-3 | | 8x+-9x=15 | | 10x^3-30x^2+15x+8=0 | | 1-3(r-7)=7 | | 8y-8=-6+7y | | 3(r-7)=7 | | -7=2k-1 | | -2x-3x+8x=9 | | 7(x+1)+4(x+1)=7x-7 | | 4(y+6)=5(y-3) | | 6x^2+9x=12 |

Equations solver categories